Klinefelter syndrome - Ibnu Pranoto, Ibnu Pranoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
A 10-year old boy presented small testicles, a small penis, hypospadia, scanty hair growth, and long legs and arms indicating Klinefelter syndrome. Klinefelter syndrome is one of the abnormality of excessive number of sex chromosomes in which the male phenotype presents female characteristics such as breast development, scanty hair growth, long arms and legs, small testes and high pitch voice.The examination in the above case reveals two X-chromosomes and one Y-chrtimosome in the nuclei of cells as the result of fertilization from XX ovum and Y spermatozoa or from X ovum with XY spermatozoa!.Â Research studies showed there were 70% XXYmale cases in which their XX chromosomes came from the mother, whereas the other 30% cases their XYchromosomes came from the father. Other studies showed the poSsible relationship of Klinefelter syndrome with the incidence of leukemia.The result of chrothosomal analysysindicates that the abOve case was trUIYKlinefelter syndrome.Key Words: Klinefelter syndrome - genital abnormality - XY chromosomes - genetic mapping - clinical generics